RI 9377 - Ultra Low Frequency Electromagnetic Fire Alarm System for Underground Mines - K. E. Hjelmstad (The National Institute for Occupational Safety and Health (NIOSH), 2010)
During an underground mine fire, air can be rapidly depleted of oxygen and contaminated with smoke and toxic fire gases. Any delay in warning miners could have disastrous consequences. Unfortunately, present mine fire alarm systems, such as stench, audible or visual alarms, telephones, and messengers, are often slow, unreliable, and limited in mine area coverage. Recent research by the U.S. Bureau of Mines has demonstrated that ultra low frequency electromagnetic signaling can be used for an underground mine fire alarm. In field tests of prototype equipment at five mines, electromagnetic signals from 630 to 2,000 Hz were transmitted through mine rock for distances as great as 1,645 m to an intrinsically safe receiver. The prototype system uses off-the-shelf components and state-of-the-art technology to insure high reliability and low cost. When utilized, this. technology would enable simultaneous and instantaneous warning of all underground personnel, regardless of their location or work activity, thereby increasing the likelihood of their successfully escaping a mine disaster. This report presents the theoretical basis for through-the-rock ultra low frequency electromagnetic transmission, design of the prototype transmitter and receiver, and the results of in-mine tests of the prototype system.